LOST IN TRANSLATION: A CRITICAL ANALYSIS OF ERRORS IN ABSTRACT TRANSLATIONS BY VOCATIONAL ACCOUNTING STUDENTS - Romadhon, Romadhon (Universitas Bunda Mulia, 2024)
This study investigates the prevalent translation errors in English abstracts written by vocational accounting students at an Indonesian polytechnic university. Given the technical nature of accounting and the growing significance of English as a global academic and business language, the ability to accurately translate complex accounting terminology is essential for students. This research aims to identify the common types of translation errors, their underlying causes, and the pedagogical implications for improving language proficiency among these students. Data were collected from a sample of 30 students who translated their Indonesian abstracts into English. The analysis focused on identifying lexical, syntactical, and grammatical errors. The findings revealed that lexical errors, such as the misuse of accounting terms, were the most frequent, followed by syntactical errors that disrupted the logical flow of sentences, and grammatical errors that undermined the readability and professionalism of the abstracts. The study highlights the challenges posed by the reliance on translation software, which often fails to capture the nuances of technical language. Practical translation exercises, peer reviews, and the use of AI-powered translation tools are recommended to enhance students' proficiency. By addressing these challenges, educators can improve the quality of academic writing among vocational students, ensuring they can effectively communicate their research findings in English. This study hopefully contributes to the development of better teaching strategies and translation support systems, ultimately preparing students for success in the global academic and professional environment.